Pesquisa de Campylobacter jejuni e Campylobacter coli em espécimes fecais de crianças com diarreia aguda e sem diarreia - Lidiane Azevedo Silva (2012)
Acute infectious diarrhea is still taken as a worldwide health problem associated with high morbidity and mortality rates among children living in developing countries. Campylobacter mainly Campylobacter jejuni and Campylobacter coli are considered major diarrheagenic agents. Besides this data regarding prevalence of the organism specially in our country is scarce. We addressed the detection of C. jejuni and C. coli in order to evaluate the contribution of the organism to the genesis of diarrhea and we also investigated the association between infection by the bacteria and clinical and demographic parameters. A total of 764 (363 with acute diarrhea and 401 without diarrhea) children aged up to 69 months of low socioeconomic stratum were included in the study. Fecal specimens were collected from 2004 to 2007 and submitted to DNA extraction. C. jejuni and C. coli were identified by two previously proposed PCR protocols. Infection by C. jejuni and C. coli was detected in 2.2% and 1.1% of children with diarrhea most of them (66.7%) C. jejuni. Any of the organisms was detected in the control group. Infection by Campylobacter was not associated with gender and age of the patient and do not showed temporal or seasonal variation. In regard to clinical parameters Campylobacter was associated with higher frequency of evacuation and bloody feces considered to be indicative of inflammatory diarrhea. Our data demonstrate lower rates of Campylobacter associated diarrhea in our population.